An investigation into menace sexual immoralities and its implications on the development of youths in Christ Apostolic Church Lagos - Segun Adediran Idowu; Opalanwo , Samuel Omoniyi; Ademola J.; Adegbite, D.D. (Corpus Intellectual, 2024)
The alarming rate of Sexual immorality among youth in our society has raised a serious concern. This menace entails lust of flesh and pleasure, which brings about humiliation and degradation to men and women. It has adversely affected remarkable virtues and good conduct in the society. In this study, sexual immorality among youth is approached from a Christian perspective in Christ Apostolic Church Grace Tabernacle DCC, Lagos State. This research employed a descriptive survey techniques. The finding revealed that Sexual immorality is prevalent among youth in Lagos state, and that Christian youths are not exempted. It is noteworthy that if Christian virtues are well upheld and Bible teachings imbibed, it will contribute to drastic reduction in the rate of sexual immoralities among youth. The study concluded that sexual immorality is a cankerworm among the youths, eating the moral and spiritual fabric of the Church. It is therefore recommended that Church leaders should take it upon themselves to educate and teach the youths about sexual morality and make them understand the need for them to be sexually pure and disciplined. Also, parents in CAC Grace Tabernacle should rise up to their responsibility in training and modeling to their children the true path of sexual purity.